Polynucleotide Phosphorylase Regulates Multiple Virulence Factors and the Stabilities of Small RNAs RsmY/Z in Pseudomonas aeruginosa - Chen, Ronghao; Weng, Yuding; Zhu, Feng; Jin, Yongxin; Liu, Chang; Pan, Xiaolei; Xia, Bin; Cheng, Zhihui; Jin, Shouguang; Wu, Weihui (Frontiers in Microbiology, 2016)
Post-transcriptional regulation enables bacteria to quickly response to environmental stresses. Polynucleotide phosphorylase (PNPase), which contains an N-terminal catalytic core and C-terminal RNA binding KH-S1 domains, is involved in RNA processing. Here we demonstrate that in Pseudomonas aeruginosa the KH-S1 domains of PNPase are required for the type III secretion system (T3SS) and bacterial virulence. Transcriptome analysis revealed a pleiotropic role of PNPase in gene regulation. Particularly, the RNA level of exsA was decreased in the ΔKH-S1 mutant, which was responsible for the reduced T3SS expression. Meanwhile, the pilus biosynthesis genes were down regulated and the type VI secretion system (T6SS) genes were up regulated in the ΔKH-S1 mutant, which were caused by increased levels of small RNAs, RsmY, and RsmZ. Further studies revealed that deletion of the KH-S1 domains did not affect the transcription of RsmY/Z, but increased their stabilities. An in vivo pull-down and in vitro electrophoretic mobility shift assay (EMSA) demonstrated a direct interaction between RsmY/Z and the KH-S1 fragment. Overall, this study reveals the roles of PNPase in the regulation of virulence factors and stabilities of small RNAs in P. aeruginosa.